Ultra-white antibacterial glass and preparation method thereof

By adopting a melting cooling method during the preparation of ultra -white antibacterial glass, the silver antibacterial agent and glass production raw materials are mixed directly to control the oxidation and reduction index, solving the problem of poor glass transmittability and antibacterial effect in existing technologies, realizing Ultra -white antibacterial glass with high light transmission and significant antibacterial effects.

CN116947314BActive Publication Date: 2025-01-24HEBEI NANBO GLASS CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310983911.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-07
Publication Date
2025-01-24
Estimated Expiration
2043-08-07

AI Technical Summary

Technical Problem

The existing ultra-white antibacterial glass is difficult to ensure the light transmittance of the glass during the preparation process, and the production cost is high, and the antibacterial effect is unstable. In particular, the ion exchange method and surface coating method have problems such as glass discoloration and poor wear resistance of the coating layer.

Method used

Using melting cooling legal preparation of ultra -white antibacterial glass. By mixing the silver antibacterial agent and glass production raw materials, the oxidation and reduction index of the control system is between 5 and 10 to ensure that the antibacterial agent is located in the three -dimensional network of the glass, and the silver ions exist in the glass Internal and surface.

Benefits of technology

The ultra -white antibacterial glass with high light transparent rate has significant antibacterial effects. Silver antibacterial agents are not vulnerable to interference by external factors. They maintain a good antibacterial effect and have a long service life.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention provides an ultra-white antibacterial glass and a preparation method thereof, belonging to the technical field of antibacterial glass. The ultra-white antibacterial glass comprises a silver antibacterial agent with good bactericidal and antibacterial effects, and is prepared by a melt cooling method. The antibacterial agent is directly mixed with glass production raw materials. In order to prevent the precipitation of silver element, the redox index of the system is controlled to be between 5 and 10 during the preparation process. The antibacterial agent is located in the three-dimensional network of the ultra-white antibacterial glass, and the antibacterial silver ions exist inside and on the surface of the glass. When acting with bacteria, the silver ions in the glass network are released by diffusion through the dissolution of the glass surface, and play an antibacterial role. Due to the protective effect of the glass network skeleton, the silver antibacterial agent is not easily disturbed and destroyed by external factors, and the ultra-white antibacterial glass can always maintain a good antibacterial effect. The ultra-white antibacterial glass of the present invention has a good visible light transmittance, and the visible light transmittance is greater than 91.56% at a thickness of 2mm, and the antibacterial rate against Escherichia coli is more than 92%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of antibacterial glass, and in particular to ultra-white antibacterial glass and a preparation method thereof. Background Art

[0002] Glass materials can be found everywhere in our daily lives, from small touch screens such as mobile phone screens and computer screens to large ones such as medical monitoring equipment, automotive glass, daily glass, and building exterior glass. When people use these glass products in daily life, they will produce sweat, dust, etc., which provide favorable conditions for the growth of bacteria. In particular, the touch screens of some electronic devices need to frequently contact with human skin, which is very easy to breed bacteria and poses certain potential hazards to human health. It is necessary to inhibit the growth and reproduction of harmful bacteria. Therefore, improving the antibacterial properties of glass materials has become a hot issue in the field of scientific research and production.

[0003] Ultra-white antibacterial glass is a product of the combination of new materials and microbiology. It uses new glass materials to inhibit or kill bacteria, adding high-tech content to traditional glass materials. Ultra-white antibacterial glass materials usually refer to glass varieties that have a strong killing rate against bacterial propagation bodies (such as Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, Bacillus subtilis, Salmonella, etc.), making it difficult for bacteria to reproduce and survive on its surface.

[0004] Ultra-white antibacterial glass mainly achieves its inhibitory effect on bacteria by adding antibacterial agents to the glass components. The antibacterial agents used include three types: inorganic metal ion type (silver ions, zinc ions, copper ions), inorganic metal oxide type (silver oxide, zinc oxide) and photocatalytic type (semiconductors represented by titanium dioxide). Among them, inorganic metal ion antibacterial agents are the most widely used due to their high antibacterial efficiency and low cost.

[0005] Among inorganic metal ion antimicrobial agents, lead ions, mercury ions, cadmium ions and other metal ions are toxic to the human body; other metal ions such as nickel, cobalt, copper and the like are coloring ions for glass, which can easily make glass products lose their colorless and transparent optical properties, and are not suitable for the production of colorless and transparent glass varieties; although zinc ions also have certain antibacterial properties, their antibacterial effect is only 0.1% of that of silver ions. Therefore, silver ions with broad-spectrum antibacterial properties and safety are the most preferred.

[0006] Silver ions have a killing effect on nearly 650 kinds of bacteria and many viruses, algae and in vitro fungi, and have a strong bactericidal and antibacterial effect. Silver-loaded ultra-white antibacterial glass uses the dissolution mechanism of silver ions as its antibacterial mechanism. When the silver-loaded glass comes into contact with bacteria, the silver ions in the glass network will detach from the network due to osmosis, penetrate the bacterial cell wall and enter the cell, and react with the functional groups such as sulfhydryl (-SH) and amino (-NH2) in the protein and nucleic acid in the bacterial cell, causing the protein to denature and inactivate, and the activity of cell synthases to decrease or even be lost, ultimately leading to the lysis of vacuoles inside the bacteria and death. After the bacteria are killed by silver ions, the silver ions are freed from the bacteria and further come into contact with other bacteria, so the silver ions have a lasting antibacterial property.

[0007] At present, the research on ultra-white antibacterial glass containing silver is mainly based on ion exchange method and surface coating method. Among them, the ion exchange method is to immerse the glass in silver ion molten salt, so that the silver ions with antibacterial function are exchanged with potassium, sodium and other ions in the glass network, thereby implanting the silver ions into the glass surface. This method is a purely chemical method. It is difficult to ensure the light transmittance of the glass in production and the actual production cost is high. If the concentration of the ion molten salt used is too high, it will also cause problems such as glass discoloration. The surface coating method is to coat a film layer with antibacterial properties on the glass surface through sol-gel technology, vacuum sputtering technology and other methods. However, the coating layer has poor wear resistance and is easy to fall off, which weakens the antibacterial performance. In addition, both methods require the introduction of additional process equipment or substantial adjustment of process parameters, which is very costly and accompanied by problems such as affecting the transmittance of the glass itself or low antibacterial effect. Summary of the invention

[0008] In view of the above-mentioned defects or deficiencies in the prior art, the present invention aims to provide an ultra-white antibacterial glass with high visible light transmittance and good antibacterial effect and a preparation method thereof.

[0009] One of the purposes of the present invention is to provide an ultra-white antibacterial glass, wherein the composition of the ultra-white antibacterial glass comprises the following components in parts by weight:

[0010] SiO2 72.1-73 parts, Na2O 13.7-14.5 parts, CaO 8.8-9.5 parts, MgO 2.8-3.5 parts, Al2O3 0.1-0.9 parts, Fe2O3 0.008-0.015 parts, K2O 0.1-0.5 parts, and antibacterial agent 0.01-0.80 parts.

[0011] The ultra-white antibacterial glass is prepared by a melt cooling method. The antibacterial agent is located in a three-dimensional network of the glass. The antibacterial agent is a silver antibacterial agent.

[0012] During the preparation of the ultra-white antibacterial glass, the redox index of the batch materials in the system is controlled to be between 5 and 10.

[0013] Preferably, the raw material of the antibacterial agent includes AgNO3.

[0014] Preferably, the redox index of the system is adjusted to between 5 and 10 by adding Na2SO4.

[0015] Preferably, the composition of the ultra-white antibacterial glass includes the following components in parts by weight:

[0016] SiO2 72.3-72.8 parts, Na2O 13.9-14.3 parts, CaO 9.1-9.4 parts, MgO 3.1-3.5 parts, Al2O3 0.2-0.6 parts, Fe2O3 0.008-0.012 parts, K2O 0.1-0.4 parts, antibacterial agent 0.01-0.60 parts.

[0017] The second object of the present invention is to provide a method for preparing ultra-white antibacterial glass, which comprises mixing glass production raw materials, melting them at high temperature and cooling them to form them.

[0018] Preferably, the glass production raw materials include the following components in parts by weight:

[0019] 70-75 parts of super white sand, 20-25 parts of soda ash, 12-17 parts of dolomite, 8-10 parts of limestone, 0.1-1 parts of aluminum hydroxide, 0.01-0.8 parts of silver nitrate, 0.8-0.9 parts of sodium sulfate, and 0.02-0.04 parts of carbon powder.

[0020] Preferably, the crystalline AgNO3 is ground into powder, passed through a 100-mesh sieve, and then added to the raw materials for glass production.

[0021] Preferably, the high temperature melting temperature is 1450° C. to 1500° C., and the high temperature melting is performed for 4 to 5 hours to obtain a glass melt.

[0022] Preferably, stirring is performed 2 to 3 times during the high-temperature melting process.

[0023] Preferably, the ultra-white antibacterial glass is cooled and formed in a graphite mold. First, the glass melt is cooled to 500-600°C, placed in an annealing furnace and kept at 550°C for 2 hours, then the glass melt is cooled to 300°C, kept for 2 hours, and then cooled to room temperature in the annealing furnace.

[0024] The beneficial effects of the present invention include:

[0025] The present invention provides an ultra-white antibacterial glass, which includes a silver antibacterial agent with good bactericidal and antibacterial effects. The ultra-white antibacterial glass is prepared by a melt cooling method, and the antibacterial agent is directly mixed with glass production raw materials. In order to prevent the precipitation of silver element, the redox index of the system is controlled to be between 5 and 10 during the preparation process. The antibacterial agent is located in the three-dimensional network of the ultra-white antibacterial glass, and the antibacterial silver ions exist inside and on the surface of the glass. When acting with bacteria, the silver ions in the glass network are released by diffusion through the dissolution of the glass surface, and play an antibacterial role. Due to the protective effect of the glass network skeleton, the silver antibacterial agent is not easily disturbed and destroyed by external factors, and the ultra-white antibacterial glass can always maintain a good antibacterial effect and a long service life. The ultra-white antibacterial glass of the present invention has a good visible light transmittance, and the visible light transmittance is greater than 91.56% at a thickness of 2mm, and the antibacterial rate against Escherichia coli is more than 92%. DETAILED DESCRIPTION

[0026] In the following description, certain specific details are included to provide a comprehensive understanding of each disclosed embodiment. However, one skilled in the relevant art will recognize that the embodiments can be implemented without one or more of these specific details, but with other methods, components, materials, etc.

[0027] Unless otherwise required herein, throughout the specification and the claims that follow, the words "include" and "comprising" should be interpreted in an open, inclusive sense, ie, "including, but not limited to."

[0028] References to "one embodiment" or "an embodiment" or "a preferred embodiment" or "certain embodiments" throughout this specification mean that the specific referenced elements, structures or features described in connection with the embodiment are included in at least one embodiment. Therefore, the phrases "in one embodiment" or "in an embodiment" or "in a preferred embodiment" or "in certain embodiments" appearing in different places throughout the specification do not necessarily all refer to the same embodiment. In addition, the specific elements, structures or features may be combined in any appropriate manner in one or more embodiments.

[0029] According to a first aspect of the present invention, there is provided an ultra-white antibacterial glass, characterized in that the composition of the ultra-white antibacterial glass comprises the following components in parts by weight:

[0030] SiO2 72.1-73 parts, Na2O 13.7-14.5 parts, CaO 8.8-9.5 parts, MgO 2.8-3.5 parts, Al2O3 0.1-0.9 parts, Fe2O3 0.008-0.015 parts, K2O 0.1-0.5 parts, and antibacterial agent 0.01-0.80 parts.

[0031] The ultra-white antibacterial glass is prepared by a melt cooling method. The antibacterial agent is located in a three-dimensional network of the glass. The antibacterial agent is a silver antibacterial agent.

[0032] In the present invention, a silver antibacterial agent with good bactericidal and antibacterial effects is used, and the antibacterial agent is directly mixed with glass production raw materials, and then prepared by a melt cooling method. The antibacterial agent is located in the three-dimensional network of the ultra-white antibacterial glass, and the antibacterial silver ions are present inside and on the surface of the glass. When reacting with bacteria, the silver ions in the glass network are released by diffusion through dissolution on the glass surface, and play an antibacterial role. Due to the protective effect of the glass network skeleton, the silver antibacterial agent is not easily disturbed and destroyed by external factors, and the ultra-white antibacterial glass can always maintain a good antibacterial effect.

[0033] In the present invention, by adjusting the formula, the antibacterial agent and the components in the formula act synergistically, and only a small amount of antibacterial agent needs to be added to achieve an antibacterial rate of more than 90%. The amount of the antibacterial agent in the ultra-white antibacterial glass is, for example, 0.01 part, 0.05 part, 0.1 part, 0.15 part, 0.2 part, 0.25 part, 0.3 part, 0.35 part, 0.4 part, 0.45 part, 0.5 part, 0.55 part, 0.6 part, 0.65 part, 0.7 part, 0.75 part or 0.8 part.

[0034] In the present invention, the amount of SiO2 in the ultra-white antibacterial glass is, for example, 72.1 parts, 72.2 parts, 72.3 parts, 72.4 parts, 72.5 parts, 72.6 parts, 72.7 parts, 72.8 parts, 72.9 parts or 73 parts.

[0035] The amount of Na2O in the ultra-white antibacterial glass is, for example, 13.7 parts, 13.8 parts, 13.9 parts, 14 parts, 14.1 parts, 14.2 parts, 14.3 parts, 14.4 parts or 14.5 parts.

[0036] The amount of CaO in the ultra-white antibacterial glass is, for example, 8.8 parts, 8.9 parts, 9 parts, 9.1 parts, 9.2 parts, 9.3 parts, 9.4 parts or 9.5 parts.

[0037] The amount of MgO in the ultra-white antibacterial glass is, for example, 2.8 parts, 2.9 parts, 3 parts, 3.1 parts, 3.2 parts, 3.3 parts, 3.4 parts or 3.5 parts.

[0038] The amount of Al2O3 in the ultra-white antibacterial glass is, for example, 0.1 part, 0.2 part, 0.3 part, 0.4 part, 0.5 part, 0.6 part, 0.7 part, 0.8 part or 0.9 part.

[0039] The amount of Fe2O3 in the ultra-white antibacterial glass is, for example, 0.008 parts, 0.009 parts, 0.01 parts, 0.011 parts, 0.012 parts, 0.013 parts, 0.014 parts or 0.015 parts.

[0040] The amount of K2O in the ultra-white antibacterial glass is, for example, 0.1 part, 0.15 part, 0.2 part, 0.25 part, 0.3 part, 0.35 part or 0.4 part.

[0041] During the preparation of the ultra-white antibacterial glass, the redox index of the batch materials in the system is controlled to be between 5 and 10.

[0042] In the present invention, in order to prevent the precipitation of silver, the redox index of the batch material in the system is controlled to be between 5 and 10 during the preparation process. When the redox index is less than 5, silver ions are easily reduced to silver in a reducing atmosphere, resulting in point impurities inside the glass. When the redox index is greater than 10, the oxidizing atmosphere is too strong, which easily causes the glass to be colored, affecting the color and transmittance of the glass.

[0043] In a preferred embodiment of the present invention, the raw material of the antibacterial agent includes AgNO3.

[0044] In the present invention, AgNO3 is a crystalline structure. When AgNO3 is mixed unevenly with the glass batch material, silver-yellow colloid will be precipitated, which will color the glass and affect the light transmittance of the glass. Therefore, the particle size of AgNO3 needs to be consistent with the particle size of the batch raw material. Specifically, the crystalline AgNO3 is ground into powder and passed through a 100-mesh sieve.

[0045] In a preferred embodiment of the present invention, the redox index of the batch material in the system is adjusted to between 5 and 10 by adding Na2SO4.

[0046] In the present invention, the addition of Na2SO4 can adjust the redox index of the batch materials in the system. Specifically, it is achieved by adding sodium sulfate to the glass raw materials. The amount of sodium sulfate added is 0.8 to 0.9 parts by weight.

[0047] In a preferred embodiment of the present invention, the composition of the ultra-white antibacterial glass includes the following components in parts by weight:

[0048] SiO2 72.3-72.8 parts, Na2O 13.9-14.3 parts, CaO 9.1-9.4 parts, MgO 3.1-3.5 parts, Al2O3 0.2-0.6 parts, Fe2O3 0.008-0.012 parts, K2O 0.1-0.4 parts, antibacterial agent 0.01-0.60 parts.

[0049] In the present invention, the glass with the composition in this range has high antibacterial rate and high visible light transmittance, with the antibacterial rate against Escherichia coli reaching 95.6-96.7% and the antibacterial rate against Staphylococcus aureus reaching 99.9%. The visible light transmittance of a 2mm thick glass sample reaches 92.1-92.4%.

[0050] According to a second aspect of the present invention, a method for preparing ultra-white antibacterial glass is provided, the method comprising mixing glass production raw materials, melting at high temperature and cooling to form.

[0051] In a preferred embodiment of the present invention, the glass production raw materials include the following components in parts by weight:

[0052] 70-75 parts of super white sand, 20-25 parts of soda ash, 12-17 parts of dolomite, 8-10 parts of limestone, 0.1-1 parts of aluminum hydroxide, 0.01-0.8 parts of silver nitrate, 0.8-0.9 parts of sodium sulfate, and 0.02-0.04 parts of carbon powder.

[0053] In a preferred embodiment of the present invention, crystalline AgNO3 is ground into powder, passed through a 100-mesh sieve, and then added to the raw materials for glass production.

[0054] In a preferred embodiment of the present invention, the high temperature melting temperature is 1450° C. to 1500° C., and the high temperature melting is performed for 4 to 5 hours to obtain a glass melt.

[0055] In a preferred embodiment of the present invention, stirring is performed 2 to 3 times during the high-temperature melting process.

[0056] In a preferred embodiment of the present invention, the ultra-white antibacterial glass is cooled and formed in a graphite mold. First, the glass melt is cooled to 500-600°C and placed in an annealing furnace for 2 hours. Then, the glass melt is cooled to 300°C, kept for 2 hours, and then cooled to room temperature in the annealing furnace.

[0057] Specifically, the method for preparing the ultra-white antibacterial glass comprises:

[0058] First, the raw materials for glass production are weighed respectively and mixed evenly to obtain a batch material;

[0059] Then, the batch material is placed in a high temperature furnace at 1450°C to 1500°C for melting. To ensure uniform melting of the batch material, it is stirred 2 to 3 times during the melting process. The melting is performed for 4 to 5 hours to obtain a glass melt.

[0060] Then, pour the glass melt into a preheated graphite mold for molding, first cool it to 500-600°C, put it into an annealing furnace, keep it at 550°C for 2 hours, then cool it to 300°C, keep it at this temperature for another 2 hours, and then cool it to room temperature with the furnace to obtain ultra-white antibacterial glass.

[0061] Example

[0062] The present invention is further described in detail below in conjunction with the embodiments. It is to be understood that the specific embodiments described herein are only used to explain the relevant invention, rather than to limit the invention. It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments can be combined with each other.

[0063] Example 1

[0064] The chemical composition of the ultra-white antibacterial glass, by weight, is 72.1 parts of SiO2, 13.7 parts of Na2O, 8.8 parts of CaO, 2.8 parts of MgO, 0.1 parts of Al2O3, 0.008 parts of Fe2O3, 0.1 parts of K2O, and 0.01 parts of silver antibacterial agent.

[0065] The preparation method is specifically as follows:

[0066] (1) 72.1 parts of ultra-white sand, 22.83 parts of soda ash, 12.88 parts of dolomite, 9.04 parts of limestone, 0.15 parts of aluminum hydroxide, 0.01 parts of silver nitrate, 0.8 parts of sodium sulfate, and 0.03 parts of carbon powder were weighed separately and mixed uniformly to obtain a batch material. The redox index of the batch material was 7.84.

[0067] (2) melting the batch material in a high-temperature furnace at 1450° C., stirring for 3 times, and melting for 5 hours to obtain a glass melt;

[0068] (3) pouring the glass melt into a preheated graphite mold for forming, cooling to 500°C, placing it in an annealing furnace, keeping it at 550°C for 2 hours, then cooling it to 300°C, and then cooling it to room temperature with the furnace after keeping it at this temperature for another 2 hours, thereby obtaining an antibacterial ultra-white glass.

[0069] The ultra-white antibacterial glass produced was tested by SGS-CSTC Standards Technical Services Co., Ltd. and found that its antibacterial rate against Escherichia coli reached 92.0%, its antibacterial rate against Staphylococcus aureus reached 99.9%, and its visible light transmittance of 2mm thick glass samples reached 92.9%.

[0070] Example 2

[0071] The chemical composition of the ultra-white antibacterial glass, by weight, is 72.3 parts of SiO2, 13.9 parts of Na2O, 9.1 parts of CaO, 3.1 parts of MgO, 0.2 parts of Al2O3, 0.01 parts of Fe2O3, 0.2 parts of K2O, and 0.2 parts of silver antibacterial agent.

[0072] The preparation method is specifically as follows:

[0073] (1) 72.3 parts of ultra-white sand, 23.16 parts of soda ash, 14.26 parts of dolomite, 8.81 parts of limestone, 0.31 parts of aluminum hydroxide, 0.2 parts of silver nitrate, 0.81 parts of sodium sulfate, and 0.03 parts of carbon powder were weighed separately and mixed uniformly to obtain a batch material. The redox index of the batch material was 8.29;

[0074] (2) melting the above batch materials in a high temperature furnace at 1475° C., stirring twice, and melting for 4.5 hours to obtain a glass melt;

[0075] (3) The glass melt is poured into a preheated graphite mold, cooled to 550°C, placed in an annealing furnace, kept at 550°C for 2 hours, then cooled to 300°C, and then cooled to room temperature with the furnace after another 2 hours of keeping warm, thereby obtaining an antibacterial ultra-white glass.

[0076] The ultra-white antibacterial glass produced was tested by SGS-CSTC Standards Technical Services Co., Ltd. and found that its antibacterial rate against Escherichia coli reached 95.6%, its antibacterial rate against Staphylococcus aureus reached 99.9%, and its visible light transmittance of 2mm thick glass sample reached 92.4%.

[0077] Example 3

[0078] The chemical composition of the ultra-white antibacterial glass, by weight, is 72.8 parts of SiO2, 14.3 parts of Na2O, 9.4 parts of CaO, 3.5 parts of MgO, 0.6 parts of Al2O3, 0.012 parts of Fe2O3, 0.4 parts of K2O, and 0.40 parts of antibacterial agent.

[0079] The preparation method is specifically as follows:

[0080] (1) 72.8 parts of ultra-white sand, 23.83 parts of soda ash, 16.1 parts of dolomite, 8.33 parts of limestone, 0.92 parts of aluminum hydroxide, 0.4 parts of silver nitrate, 0.83 parts of sodium sulfate, and 0.03 parts of carbon powder were weighed separately and mixed uniformly to obtain a batch material, and the redox index of the batch material was 8.44;

[0081] (2) melting the above batch materials in a high temperature furnace at 1500° C., stirring twice, and melting for 4 hours to obtain a glass melt;

[0082] (3) The glass melt is poured into a preheated graphite mold, cooled to 600°C, placed in an annealing furnace, kept at 550°C for 2 hours, then cooled to 300°C, and then cooled to room temperature with the furnace after another 2 hours of keeping warm, thereby obtaining antibacterial ultra-white glass.

[0083] The ultra-white antibacterial glass produced has an antibacterial rate of 96.7% against Escherichia coli and 99.9% against Staphylococcus aureus after being tested by SGS. The visible light transmittance of the 2mm thick glass sample is 92.1%.

[0084] Example 4

[0085] The chemical composition of the ultra-white antibacterial glass, by weight, is 73.0 parts of SiO2, 14.5 parts of Na2O, 9.5 parts of CaO, 3.5 parts of MgO, 0.9 parts of Al2O3, 0.015 parts of Fe2O3, 0.5 parts of K2O, and 0.80 parts of antibacterial agent.

[0086] The preparation method is specifically as follows:

[0087] (1) 73 parts of ultra-white sand, 24.16 parts of soda ash, 16.1 parts of dolomite, 8.52 parts of limestone, 1.38 parts of aluminum hydroxide, 0.8 parts of silver nitrate, 0.85 parts of sodium sulfate, and 0.03 parts of carbon powder were weighed separately and mixed uniformly to obtain a batch material, and the redox index of the batch material was 8.62;

[0088] (2) melting the above batch materials in a high temperature furnace at 1480° C., stirring twice, and melting for 4 hours to obtain a glass melt;

[0089] (3) The glass melt is poured into a preheated graphite mold for molding, cooled to 560°C, placed in an annealing furnace, kept at 550°C for 2 hours, then cooled to 300°C, and then cooled to room temperature with the furnace after being kept at this temperature for another 2 hours to obtain antibacterial ultra-white glass.

[0090] The ultra-white antibacterial glass produced has an antibacterial rate of 97.5% against Escherichia coli and 99.9% against Staphylococcus aureus after being tested by SGS. The visible light transmittance of the 2mm thick glass sample is 91.56%.

[0091] Comparative Example 1

[0092] The chemical composition of the ultra-white antibacterial glass, by weight, is 72.8 parts of SiO2, 14.15 parts of Na2O, 9.4 parts of CaO, 3.5 parts of MgO, 0.6 parts of Al2O3, 0.012 parts of Fe2O3, 0.4 parts of K2O, and 0.40 parts of antibacterial agent.

[0093] The preparation method is specifically as follows:

[0094] The amount of sodium sulfate added was 0.5 parts, and the other parts were the same as in Example 3. The redox index of the batch was 2.36.

[0095] The obtained ultra-white antibacterial glass has dot-shaped silver element precipitation.

[0096] Comparative Example 2

[0097] The chemical composition of the ultra-white antibacterial glass, by weight, is 72.8 parts of SiO2, 14.20 parts of Na2O, 9.4 parts of CaO, 3.5 parts of MgO, 0.6 parts of Al2O3, 0.012 parts of Fe2O3, 0.4 parts of K2O, and 0.40 parts of antibacterial agent.

[0098] The preparation method is specifically as follows:

[0099] The amount of sodium sulfate added was 0.6 parts, and the other parts were the same as in Example 3. The redox index of the batch was 4.20.

[0100] The obtained ultra-white antibacterial glass has dot-shaped silver element precipitation.

[0101] This article uses specific examples to illustrate the principles and implementation methods of this application. The description of the above embodiments is only used to help understand the method and its core ideas of this application. The above is only the preferred implementation method of this application. It should be pointed out that due to the limitations of textual expression and the objective existence of infinite specific structures, ordinary technicians in this technical field can make several improvements, modifications or changes without departing from the principles of the present invention, and can also combine the above technical features in an appropriate manner; these improvements, modifications, changes or combinations, or the direct application of the inventive concept and technical solution to other occasions without improvement, should be regarded as the scope of protection of this application.

Claims

1. An ultra-white antibacterial glass, characterized in that: The ultra-white antibacterial glass is composed of the following components in parts by weight: SiO2 72.1~73 parts, Na2O 13.7~14.5 parts, CaO 8.8~9.5 parts, MgO 2.8~3.5 parts, Al2O3 0.1~0.9 parts, Fe2O3 0.008~0.015 parts, K2O 0.1~0.5 parts, and antibacterial agent 0.01~0.80 parts; The ultra-white antibacterial glass is prepared by a melt cooling method, the antibacterial agent is located in a three-dimensional network of the glass, and the antibacterial agent is a silver antibacterial agent; In order to prevent the precipitation of silver, the redox index of the batch materials in the system is controlled to be between 5 and 10 during the preparation process of the ultra-white antibacterial glass; The raw materials of the antibacterial agent include AgNO3, and the crystalline AgNO3 is ground into powder, passed through a 100-mesh sieve, and then added into the raw materials for glass production; The preparation method of the ultra-white antibacterial glass comprises mixing glass production raw materials, melting at high temperature and cooling to form, wherein the temperature of the high temperature melting is 1450° C. to 1500° C.; The ultra-white antibacterial glass is cooled and formed in a graphite mold. First, the glass melt is cooled to 500-600°C, placed in an annealing furnace and kept at 550°C for 2 hours, and then the glass melt is cooled to 300°C, kept at this temperature for 2 hours, and then cooled to room temperature in the annealing furnace.

2. The ultra-white antibacterial glass according to claim 1, characterized in that: By adding Na2SO4, the redox index of the system is adjusted to between 5 and 10.

3. The ultra-white antibacterial glass according to claim 1, characterized in that: The composition of the ultra-white antibacterial glass includes the following components in parts by weight: SiO2 72.3~72.8 parts, Na2O 13.9~14.3 parts, CaO 9.1~9.4 parts, MgO 3.1~3.5 parts, Al2O3 0.2~0.6 parts, Fe2O3 0.008~0.012 parts, K2O 0.1~0.4 parts, antibacterial agent 0.01~0.60 parts.

4. The ultra-white antibacterial glass according to claim 1, characterized in that: The glass production raw materials include the following components in parts by weight: 70-75 parts of super white sand, 20-25 parts of soda ash, 12-17 parts of dolomite, 8-10 parts of limestone, 0.1-1 parts of aluminum hydroxide, 0.01-0.8 parts of silver nitrate, 0.8-0.9 parts of sodium sulfate, and 0.02-0.04 parts of carbon powder.

5. The ultra-white antibacterial glass according to claim 1, characterized in that: The high temperature melting time is 4 to 5 hours to obtain a glass melt.

6. The ultra-white antibacterial glass according to claim 1, characterized in that: During the high temperature melting process, stir 2 to 3 times.

Citation Information

Patent Citations

  • Antibacterial float glass

    CN1803684A